Dermoscopy of Lichen Planus Pigmentosus and Histopathological Correlation: A Case Series - Amal Chamli; Malek Mrad; Houda Hammami; Imen Helal; Anissa Zaouak; Samy Fenniche (Mattioli1885, 2024)
Introduction: Lichen planus pigmentosus (LPP) is an acquired pigmentary disorder affecting the dark-skinned population. There is a wide range of differentials with substantial clinicopathological overlap. Dermoscopy may contribute to the better characterization of this dermatosis. Objective: This study aimed to describe dermoscopic features of LPP with a histopathological correlation. Methods: LPP lesions of 23 patients were studied using a polarized dermoscopy, followed by histological evaluation. Results: The most common dermoscopic finding was dots and/or globules (n=23) in different patterns: speckled (n=4), dotted (n=2), reticular (n=4), diffuse (n=9), hem-like (n=1), and circular (n=2). Other patterns were exaggerated pseudo-reticular pattern (n=12), sparing of follicular openings (n=23), targetoid appearance (n=3), blue-white veil (n=5), rosettes (n=5), erythema (n=4), and telangiectasia (n=7). Histological findings included pigment incontinence (n=23), the severity being mild (n=8) and severe (n=15). We found a statistically significant association between the intensity of pigmentary incontinence on the histological examination and the presence of blotches in dermoscopy (p=0.046); and between blue-white veil and rosettes in flexural areas (p=0.01). Also, a statistical relationship was found between severe pigment density (reticulated and diffused patterns) and a short disease duration (p=0.016). Conclusion: We described LPP dermoscopic changes according to disease progression. We found that blotches are indicative of long-duration disease and could be specific dermoscopic features of LPP. We demonstrated that a blue-white veil associated with rosettes could be pathognomonic features of LPP inversus.